THE CHARACTERISTICS AND ANTIOXIDANT ACTIVITIES OF CHABA MAPLE (HIBISCUS ACETOSELLA) HOMEMADE JAM - THUNGMUNGMEE, SURADWADEE; WISIDSRI, NAKUNTWALAI; KHOBJAI, WARACHATE; DUMRONGPHUTTIDECHA, THISAKORN; JAMKOM, KHEMJIRA; TECHAEOI, SURACHAI (International Journal of Applied Pharmaceutics, 2019)
Objective: This study aimed to characterize physicochemical and chemical characteristics of Chaba maple (Hibiscus acetosella) homemade jam (CHJ) and determine its autoxidation ability. Methods: The physicochemical and chemical characteristics of CHJ were investigated. The color, viscosity, and pH were observed as physicochemical data while chemical properties were obtained from sugar content and total polyphenol content (TPC), determined using high-performance liquid chromatography refractometer and Folin–Ciocalteu assay, respectively. The antioxidant activities of CHJ were identified using 1,1-diphenyl-2- picrylhydrazyl (DPPH) radical scavenging, ferric reducing antioxidant power (FRAP), and nitric oxide (NO) radical scavenging ability methods. Results: The color and viscosity of CHJ were purple-red and 34,483.33±152.75 cP, respectively. The pH was at 3.78. The total sugar was not detected in CHJ. The TPC of CHJ showed the highest (47.18±1.80 mg gallic acid equivalent [GAE]/g of jam) followed by Streamline (SL) (23.66±0.32 mg GAE/g of jam), Doikham (DK) (21.99±0.50 mg GAE/g of jam), and Best food (BF) (9.75±0.38 mg GAE/g of jam), respectively. Antioxidant activities of CHJ with %1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging of 100.00±1.39% and FRAP value of 1690.70±8.26 uM. Both of activities exhibited the highest activity and significantly different when compared with other jams. The %NO scavenging activity of CHJ and SL was 72.43±1.93% and 73.82±1.66%, respectively, which higher than DK and BF. Conclusion: This study shows good in both physicochemical and chemical characteristics of CHJ. The CHJ presents the highest TPC as well as antioxidant activities. Thus, a homemade jam of Chaba maple may be considered as a good source of antioxidants and functional foods.